Resources of Water - Thanjavur Chandrasekaran, Prathna; Salik Javaid, Muhammad; Sadiq, Aftab (IntechOpen, 2021)
Water is a limited natural resource indispensable for human existence. Water resources exist in the form of glaciers, oceans, rainwater, groundwater, and surface water. Uncontrolled population growth, urbanization, and inefficient management of natural resources have hastened the pace and impact of climate change. Floods and droughts related to climate change occur more frequently, destructing the livelihood of people and disrupting the fragile ecosystem. The need for conservation of available water resources and devising strategies for resource management is very relevant in the current scenario and this book deals precisely with water resources and their management. It provides abundant and relevant information on all aspects related to water resources, including the need for conservation, water management strategies in different parts of the world, the impact of climate change on water management, pollution of water resources and treatment, and so forth. The book will motivate readers and scientists alike to look further and make concerted efforts towards promoting the preservation and conservation of water resources.